Rake. Series 3 [videorecording (DVD)] - Duncan, Peter, 1964-; Day, Matt, 1971-; Dykstra, Russell; Cormack, Danielle (Acorn : RLJ Entertainment, 2017)
Cleaver languishes in jail, facing the consequences of his crimes and misbehaviors, while he awaits the outcome of his appeal. When the conviction is quashed at last, he discovers his world has grown even more chaotic in his absence. The proliferation of Royal Commissions, inquiries and corruption trials requires so many barristers, even Cleaver can find work. Of course, Cleaver being Cleaver, he finds himself at the heart of a billion dollar criminal, political and moral dilemma.